2018
DOI: 10.2503/hortj.okd-130
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low Temperature, Shading, Defoliation, and Crop Load on the Flesh Coloration of the Type 2 Red-fleshed Apple ‘Kurenainoyume’

Abstract: Kurenainoyume' is a newly released type 2 red-fleshed apple with pinkish flesh color. In our previous study, we revealed the effects of light condition on red coloration of the skin, flesh, and core of 'Kurenainoyume' apple fruit. In this study, we investigated the effects of temperature, shading, defoliation, and crop load on red coloration of the flesh. Low temperature improved flesh coloration; apples subjected to cooling treatment at 5°C or 10°C showed higher a* values of the Lab color space than the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…In general, skin color as well as flesh color tends to deteriorate in apple trees with active vegetative growth, which indicates that too much soil nitrogen has a negative impact on anthocyanin accumulation. In addition, cooler climate conditions are advantageous for flesh coloration in 'Kurenainoyume' (Matsumoto et al, 2018b). Honda et al (2014Honda et al ( , 2017 also showed the effect of cooler temperature on the flesh red coloration in 'Pink Pearl'.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, skin color as well as flesh color tends to deteriorate in apple trees with active vegetative growth, which indicates that too much soil nitrogen has a negative impact on anthocyanin accumulation. In addition, cooler climate conditions are advantageous for flesh coloration in 'Kurenainoyume' (Matsumoto et al, 2018b). Honda et al (2014Honda et al ( , 2017 also showed the effect of cooler temperature on the flesh red coloration in 'Pink Pearl'.…”
Section: Discussionmentioning
confidence: 99%
“…The one-layer white bag had 0.9-2.3% light permeability from 280-750 nm wavelength, while the 1-layer red bag had lower light permeability of 280-575 nm compared to the 1-layer white bag, but its light permeability of 576-750 nm was higher than the 1-layer white bag (Matsumoto et al, 2018b). Half of each paper bags were removed at 100 DAFB (August 20) (bag-removal treatment) and the remaining half were covered continuously until the final harvest at 139 DAFB (September 28) (continuous-bagging treatment).…”
Section: Effect Of Fruit Bagging Treatment With Different Light Permementioning
confidence: 99%
“…They reported decreased anthocyanin concentration as crop load increased, or for bagged vs. un-bagged fruit or for fruit grown in the shade vs. that exposed to the sun. Similarly, [15] found decreased red color in the outer flesh as indexed by the a-value of the flesh when the fruit was shaded (by bagging), when crop load was high or when trees were defoliated. When bags were removed, color intensity increased again in the outer flesh.…”
Section: Light Stimulation Of Anthocyanin Biosynthesismentioning
confidence: 83%
“…Thus, cool water treatment of the fruit during developmental stage was effective for flesh coloration (Matsumoto et al, 2018a); however, such effects were not recorded in the harvested fruit during cold storage. The skin color of the harvested apples such as 'Tsugaru' and 'Fuji' may be generally promoted by cold treatment (Bai et al, 2014;Ban et al, 2007;Ubi et al, 2006).…”
Section: Effect Of Cold Storage On the Skin And Flesh Colorationmentioning
confidence: 99%
“…Therefore, it is desirable to provide information about the storability of 'Kurenainoyume' and changes in the parameters related to fruit quality such as skin/flesh coloration, flesh firmness, soluble solid content, and acidity during cold storage to all growers. In our previous reports, we showed an improvement in the flesh red coloration by low temperature treatment during the growing stage (Matsumoto et al, 2018a), which suggests the possibility of improvement in the flesh red coloration by cold storage after harvest. However, there are few available reports on the changes in the parameters related to fruit quality, including changes in the skin and flesh coloration in red-fleshed type 2 apples .…”
Section: Introductionmentioning
confidence: 99%